2011
DOI: 10.1039/c0cc05054g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of ADP over ATP in aqueous solution by a polyammonium receptor containing a pyrimidine residue

Abstract: The synergistic action of the different binding groups of the polyfunctional HL receptor leads to the recognition of ADP over ATP in water, with a selectivity coefficient of up to 116, a phenomenon which is unprecedented in the context of synthetic receptors in water. The recognition is mostly due to the good matching between H(3)L(2+) and the protonated forms of ADP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Fluorescent sensing of biological anions has drawn much attention in recent years [35][36][37]. Thus 1-Cu 2+ complex was prepared in situ by mixing 1 with Cu(ClO 4 ) 2 at a 1:3 ratio in aqueous solution, and its fluorescent emission in the presence of various anions was examined.…”
Section: Fluorescent Signaling Of Adp By 1-cu 2+mentioning
confidence: 99%
“…Fluorescent sensing of biological anions has drawn much attention in recent years [35][36][37]. Thus 1-Cu 2+ complex was prepared in situ by mixing 1 with Cu(ClO 4 ) 2 at a 1:3 ratio in aqueous solution, and its fluorescent emission in the presence of various anions was examined.…”
Section: Fluorescent Signaling Of Adp By 1-cu 2+mentioning
confidence: 99%
“…Obviously, AMP does not effectively interact with the two distally located binding sites of the calixarenes and is not able to expel the dianionic dye from the aggregates. A quite different picture is observed for ADP and ATP, which are present in the dianionic and trianionic form at pH 6.5 [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…This receptor showed a stronger binding of AMP in comparison with ADP and ATP [ 11 ]. Another polyammonium receptor synthesized by Mascaros et al [ 12 ] showed selective recognition of ADP in the presence of ATP in water.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of the first binding site through stacking interactions with the second site is likely to be the simplest and most abundant solution in any random pool, due to its minimal sequence requirements, and we are challenged to design selection conditions to avoid this “tyranny of short motifs” 4c. From the perspective of sensors and receptors for nucleotides,5 it would be of interest to identify a single‐site receptor that would have more tunable interactions with adenosine analogues, for example, such that aptamer selectivity could be varied. This ability would immediately lead to small cross‐reactive arrays6 for monitoring adenosine balance, and possibly also to a series of more‐specific sensors.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure selected against variants of the full‐length DH motif. Alternative binding pockets were further disfavored by a counter selection5 with adenosine analogue linked at the N6 position to agarose (Scheme ). This selects against any motif that, unlike the DH motif, can accommodate substitutions at the N6 position 1.…”
Section: Methodsmentioning
confidence: 99%